The Ngäbe People of Sixaola: A Socioterritorial Movements Perspective on the Struggle of a Transborder Indigenous People without Territory - Mora-Calderón, José Antonio (2026)
Introduction: The Ngäbe people of Sixaola constitute a transboundary Indigenous community facing a range of social and environmental challenges stemming from the absence of an officially recognized Indigenous territory. In response, the community has undertaken a series of collective actions to demand that the Costa Rican state fulfill their ancestral right to land and territory. Objective: To analyze the struggle for the creation of an Indigenous territory for the Ngäbe people of Sixaola, framed through the theoretical lens of socio-territorial movements. Method and Technique: A documentary review based on the analysis of bibliographic and hemerographic sources was conducted. First, available bibliographic material was reviewed; subsequently, hemerographic information was systematized due to the limited availability of specific scholarly literature on this Indigenous group. Results: The spatial configuration of the various Ngäbe groups in Costa Rica and Panama was characterized, and relevant bibliographic sources on social and socio-territorial movements were identified. Four main categories of issues faced by the Ngäbe people of Sixaola were documented. The community’s territorial struggle was analyzed through the characterization of their claims and the repertoire of collective actions undertaken. Conclusions: The struggle for territorial recognition by this Indigenous community can be understood within the framework of socio-territorial movements, as the core of their political agency centers on the urgent need to initiate a process of territorialization.